2012
DOI: 10.3892/mmr.2015.3546
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA-125a-5p, a useful biomarker in liver diseases, correlates with disease progression

Abstract: Abstract. It has be en demonst rated t hat l iver microRNA-125a-5p (miR-125a-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Coppola et al [18] further indicated that liver miR-125a-5p is correlated with HBV replication and disease progression in chronic hepatitis B patients. Our previous study demonstrated that serum miR-125a-5p may be a non-invasive biomarker for predicting disease progression in human liver diseases [19]. Here we report that miR-125a-5p is up-regulated in mice with liver fibrosis and activated HSCs, in line with the results obtained in humans.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Coppola et al [18] further indicated that liver miR-125a-5p is correlated with HBV replication and disease progression in chronic hepatitis B patients. Our previous study demonstrated that serum miR-125a-5p may be a non-invasive biomarker for predicting disease progression in human liver diseases [19]. Here we report that miR-125a-5p is up-regulated in mice with liver fibrosis and activated HSCs, in line with the results obtained in humans.…”
Section: Discussionsupporting
confidence: 81%
“…Compared with the control, an increased level of miR125a-5p was observed in liver fibrosis (Fig. 1D), consistent with previous results in humans [18,19].…”
Section: Mir-125a-5p Is Up-regulated In Liver Fibrosis and Activated supporting
confidence: 81%
See 1 more Smart Citation
“…MiR-125a-5p is also involved in lipid metabolism [ 91 ] and its level has been found increased in hyperlipidemic and/or hyperglycemic patients’ sera [ 92 ]. MiR-125a-5p serum levels have been also described as biomarkers in liver diseases [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, HCC patients with low levels of miR-665 showed a strong association with large tumour size (> 5 cm), local tumour invasion and metastases [74] ; Shi et al [75] showed that decreased levels of exosomal miR-638 had poor OS. Zheng et al [76] reported that low levels of serum miR-125a-5p were associated with a lower OS compared with those exhibiting higher expression levels, and more recently Liu et al [77] confirmed by a Kaplan-Meier analysis that HCC patients with lower serum miR-125b levels showed reduced time to recurrence and OS. Many studies involved the analysis of circulating miR-21.…”
Section: Circulating Mirnas For Hcc Prognosismentioning
confidence: 96%